Prayer for a child - Field, Rachel, 1894-1942.; Jones, Elizabeth Orton, 1910-2005. (New York : Simon & Schuster Books for Young Readers, 2005)
For sixty years children and parents have shared in the joy and inspiration of Rachel Field and Elizabeth Orton Jones's Prayer for a Child. This new edition commemorates the diamond anniversary of the award-winning modern classic's original publication.
Originally published: New York Macmillan, 1944.
Keywords: Caldecott Medal; Bedtime prayers; Children -- Prayer-books and devotions -- English